Estudo, construção e caracterização de diodos orgânicos tipo Schttky - Carr, Olivia [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
During the twentieth century the inorganic electronics was largely developed being present in various industrial equipment or household use. However, at the end of that century were verified electronic properties in organic compounds, giving rise to the field of organic electronics. Since then, the physical properties of elementary devices such as diodes and organic transistors have been studied. In this work was studied the properties of diode devices fabricated with a semiconductor polymer, the poly-o-methoxyaniline (POMA). Devices containing electrodes of Au and Al were fabricated with semiconductor polymer of different doping levels. We found that the rectifying behavior for the heterojunctions metal/polimer are reached only for high doping level (with conductivity greater than 1,77. 10-9 S / cm), which gives the devices characteristic of a Schottky diode. The rectifying behavior was observed for electric fields of low magnitude, below the operating field (~ 600 V/cm), while for electric field greater than 600 V/cm the a linear behavior I vs.V was obtained. We determined that this Ohmic behavior arises from the charge transport over the volume of the semiconductor material after the lowering of the metal/semiconductor barrier. In devices with weakly doped semiconductor, the electrical resistance of the volume becomes high and the process of charge transportation is dominated by the volume, for any intensity of the applied electric field

Durante o século XX a eletrônica inorgânica foi amplamente desenvolvida resultando em diversos equipamentos de uso industrial ou doméstico de nosso dia-a-dia. Entretanto, no final do mesmo século foram verificadas propriedades eletrônicas em compostos orgânicos, dando origem ao campo da eletrônica orgânica. Desde então as propriedades físicas de dispositivos elementares, como diodos e transistores orgânicos, vêm sendo estudadas. Neste trabalho estudamos as propriedades de dispositivos de heterojunção fabricados com o polímero semicondutor poli-o-metóxianilina (POMA). Os dispositivos contendo eletrodos de Au e Al foram fabricados com material semicondutor com diferentes níveis de dopagem. Verificamos que as heterojunções são retificadoras apenas para dispositivos fabricados com semicondutor com elevado nível de dopagem (com condutividade superior a 1,77. 10-9 S/cm), conferindo aos dispositivos características de diodo tipo Schottky. Observou-se comportamento retificador para campos elétricos com baixa magnitude, abaixo do campo de operação (~ 600 V/cm), enquanto que para campo elétrico com magnitude superior à de operação um comportamento I vs. V linear foi obtido. Determinamos que este comportamento ôhmico tem origem no trânsito de lacunas através do volume do material semicondutor. Em dispositivos com o semicondutor fracamente dopado, a resistência elétrica do volume se torna elevada sendo o processo de transporte de cargas dominado pelo volume, para qualquer intensidade de campo elétrico aplicado
Keywords: Semicondutores; Diodos semicondutores; Fisica; Semicondutores - Propriedades físicas